2007
DOI: 10.1097/yct.0b013e31811f354c
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Substrates of Electroconvulsive Therapy for Tourette Syndrome

Abstract: We report the case of an adult male patient with Tourette syndrome, self-injurious behavior and depression, refractory to conventional treatment, and whose symptoms remitted after electroconvulsive therapy. Serial Technetium 99m-Ethyl-Cysteinate-Dimer single photon emission tomographies were applied, before, during, and after electroconvulsive therapy. The neural substrates of this treatment process were further analyzed by woxel-wise subtracted single photon emission tomography images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…8 Electroconvulsive therapy is a noninvasive electrical stimulation therapy that influences cortical excitability. 11,12,14 These strong comorbidities clearly reduced the conclusiveness of a specific efficacy of ECT, although it was considered an effective treatment for the therapyrefractory GTS symptoms in 6 of the patients. The 7 reports on GTS and ECT (Table 1) 9Y15 in the literature noted that 5 of the 7 patients suffered not only from GTS but also from psychotic symptoms 10,15 or depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Electroconvulsive therapy is a noninvasive electrical stimulation therapy that influences cortical excitability. 11,12,14 These strong comorbidities clearly reduced the conclusiveness of a specific efficacy of ECT, although it was considered an effective treatment for the therapyrefractory GTS symptoms in 6 of the patients. The 7 reports on GTS and ECT (Table 1) 9Y15 in the literature noted that 5 of the 7 patients suffered not only from GTS but also from psychotic symptoms 10,15 or depression.…”
Section: Discussionmentioning
confidence: 99%
“…14 Tardive GTS + MD 1 59 M 4Â bilateral, 6Â unilateral Total resolution of a severe motor tic Rapoport 12 GTS + MD 1 37 F 8Â unilateral Tics were in full remission Trivedi 15 GTS + catatonia 1 64 F 6Â bilateral Tics responded rapidly Strassnig 13 GTS 1 39 F 9Â unilateral, 12Â M-ECT Remarkably positive effects on tic symptoms Karadenizli 10 GTS + auditory hallucinations 1 28 M 7Â bilateral A 2-year remission in symptoms Morais 11 GTS + MD 1 27 M 15Â bilateral, 8Â M-ECT Complete remission of tics and depression As a first step, controlled studies with short-term and long-term observation of patients with GTS are required to ensure the efficacy of this well-tolerated and noninvasive treatment in this special patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement rates between 83-100% were reported; thus, all four patients achieved clinical response [44][45][46][47]. Qualitative follow-up outcomes were reported in three cases: all experienced complete remission with no relapse up to 8 months following treatment [44][45][46], yet no studies reported quantitative (i.e., YGTSS) outcomes at follow-up. Depression outcomes were not reported, despite two patients reportedly experiencing comorbid depression.…”
Section: Ect Results For Tsmentioning
confidence: 99%
“…There has been limited data on the effects of ECT on patients with Tourette's syndrome or other tic-like disorders. During this review, there were eight case reports of patients with tic-like disorders, including Tourette's, being treated with ECT [47][48][49][50][51][52][53][54]. There was a positive effect of ECT in all cases regardless of lead placement, such as a two-year remission after seven ECT sessions [49], the elimination of any symptoms of Gilles de la Tourette's syndrome for five months after ECT [52], and the resolution of symptomology in a patient who suffered both from obsessive-compulsive disorder and Tourette's syndrome [54].…”
Section: Tourette's and Other Tic-like Disordersmentioning
confidence: 99%